A study on scaled up proton exchange membrane fuel cell with various flow channels for optimizing power output by effective water management using numerical technique. (15th October 2016) - Arun Saco, S.; Thundil Karuppa Raj, R.; Karthikeyan, P.
Abstract: Water management in a Proton Exchange Membrane Fuel Cell (PEMFC) is of great concern for effective cell performance. Existing studies for scaled up model of PEMFC are limited only to experimental work where effective water management with respect to flow channels are very few, time consuming and less economical. In this connection, an extensive numerical study is carried out for optimizing the flow channels with respect to optimal pressure drop and water management for the scaled up model (225 cm 2 ) of PEMFC which is a novel approach in the field of PEMFC. This numerical study involves four different configurations of flow channels. In the first configuration, predominantly existing serpentine parallel flow channel for 25 cm 2 is extended to 225 cm 2 cross-sectional area. Serpentine zig-zag, straight parallel and straight zig-zag are the other three flow channels considered respectively in this study. The three dimensional flow through the PEMFC is simulated by solving the governing principles namely mass, momentum, energy, species and electro-chemical equations. It is found that the power density developed by straight flow channel with zig-zag flow path is 0.3758 W/cm 2 and is the maximum of the configurations considered and this is due to effective water management with minimal pressure drop. Highlights: Scaled-up proton exchange membrane fuel cell flow channel is optimized numerically. Novel approach of uniformly distributed straight zig-zag flow channel is analysed. Water management and proton conductivity on scaled up fuel cell is investigated. Pressure drop characteristics for various flow channel configuration is presented. Hydrogen, oxygen and water concentration is analysed for various flow channels.